Pemanfaatan Media Sosial Sebagai Alat Komunikasi Dalam Meningkatkan Efektivitas Dakwah di Era Digital - I, Ilham; Muliana, Sri; Sihombing, Suci Muthia; Rahmitha, Suci; Sirait, Aldi Kurniawan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Social media has become an effective means of spreading da’wah messages globally. The purpose of this study is to analyze the use of social media in increasing the effectiveness of da’wah in the digital era. The results of this study are that the use of social media in da’wah has an important role and great potential. Da’wah messages can be spread quickly and effectively through social media, reaching a wider audience. However, the use of social media in da’wah must be wise and responsible. Da’wah content needs to pay attention to the truth, credibility, and context of Islamic teachings. Collaboration between kiai, santri, and wise social media users is needed. Challenges include the spread of inaccurate information and a lack of understanding of social media ethics. A wise approach and effective strategy are needed, such as ensuring the accuracy of information and increasing digital literacy. The use of social media in da’wah has complex social impacts, with benefits and negative impacts that need to be watched out for. Good understanding and wise use are very important in utilizing social media in da’wah.